Dampak Literasi Keuangan terhadap Keberlanjutan Bisnis dengan Finacial Inclusion sebagai Faktor Mediasi - Ita Fitria; Hasim As’ari (Income Journal: Accounting, Management and Economic Research, 2024)
Business Sustainability is the ability to achieve business goals, enhance value over the long term, and maintain consistency in preserving what has been achieved. In the era of national economic recovery, many innovative new businesses have emerged, intensifying competition in the business world. If businesses fail to enhance their capabilities in sustaining their operations, it may diminish their business value and lead to their inability to survive. This study seeks to ascertain the impact of financial literacy on the enduring nature of businesses, while considering financial inclusion as a mediating factor. The theoretical framework employed in this investigation is the Resource-Based View (RBV) theory.The population in this study consists of micro, small, and medium enterprises (MSMEs) registered with the Department of Trade, Cooperatives, and MSMEs in Wonosobo Regency. The sample size is 96 MSMEs selected using the Purposive Sampling method. The research method employed is quantitative, and data analysis is conducted using SPSS Version 26, including tests for validity, reliability, descriptive statistics, classic assumption tests, linear regression, and hypothesis testing. The findings from this study demonstrate that business sustainability is impacted by financial literacy, and that financial inclusion has a direct influence on business sustainability. Furthermore, financial literacy plays a role in shaping financial inclusion, and financial literacy indirectly affects business sustainability by means of financial inclusion.The implications of this study suggest that an increase in financial literacy can lead to improved financial inclusion, which is expected to help MSMEs maintain the sustainability of their businesses